Optimalisasi Bimbingan Belajar Berbasis Fun Learning dan Strategi Pemasaran Edukasi dalam Meningkatkan Motivasi serta Prestasi Literasi-Numerasi Anak di Kabupaten Indramayu - Fitriyani; Hanafi Alfian Luthfi, Bardan; Aulia, Friska; Khayati, Salsabila; Madonna Uli Hasibuan, Madu; Cacih; Nur Cahyani, Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low learning motivation and weak mastery of basic literacy and numeracy (calistung) among early childhood and lower primary school students are critical issues directly impacting academic achievement in Indramayu Regency. This article aims to synthesize the results of Community Service (PKM) activities from two partner locations, namely PAUD Graha Insan Mulia (Haurgeulis District) and Rumbel Siti Salamah (Kroya District). The implementation method encompasses structured learning assistance based on fun learning (storytelling, educational games, interactive quizzes), strengthening Al-Qur'an/Iqro reading, and formulating strategic educational marketing analysis (SWOT and PESTEL). The results showed a significant increase in active participation and learning motivation (>85%), improvement in independent calistung abilities, and heightened self-confidence through personal expression activities. Furthermore, the integration of SWOT and PESTEL strategies provided a sustainable framework for educational administrators to design affordable, regulatory-adaptive, and community-oriented tutoring programs.